2023
DOI: 10.3390/biology12091254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sugar Beet Pulp on the Composition and Predicted Function of Equine Fecal Microbiota

Tamara Ford,
Zachary L. McAdams,
Kile S. Townsend
et al.

Abstract: The purpose of this study is to determine the effect of the partial replacement of dietary hay with sugar beet pulp (SBP) on the composition and predicted function of the fecal microbiota of healthy adult horses. Fecal samples were collected daily for 12 days from six adult horses after removal from pasture, including a five-day acclimation period, and a seven-day period following the introduction of SBP into their diet, and compared to six untreated horses over a comparable period. Fecal DNA was subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Several studies evaluating the impact of prebiotics on the horse-hindgut microbiome have been reported, but most of them either enrolled a low number of horses per group, included many variables, evaluated different products, or were performed in vitro [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. Furthermore, it is not rare for the private companies producing those compounds to sponsor the studies, and therefore results should be interpreted with particular caution as they tend to emphasize the beneficial changes in the microbiome.…”
Section: Techniques Of Microbiota Manipulationmentioning
confidence: 99%
“…Several studies evaluating the impact of prebiotics on the horse-hindgut microbiome have been reported, but most of them either enrolled a low number of horses per group, included many variables, evaluated different products, or were performed in vitro [ 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 ]. Furthermore, it is not rare for the private companies producing those compounds to sponsor the studies, and therefore results should be interpreted with particular caution as they tend to emphasize the beneficial changes in the microbiome.…”
Section: Techniques Of Microbiota Manipulationmentioning
confidence: 99%